Sexual health communication among youth: a study of knowledge and attitude - Suffian Hadi Ayub; Mohammad Rezal Hamzah; Sharipah Nur Mursalina Syed Azmy; Wan Abdul Hayyi Wan Omar; Nor Hafizah Abdullah; Zanirah Wahab; Hishamuddin Salim (Penerbit Universiti Kebangsaan Malaysia, 2017)
Sexual health communication is currently one of the most discussed topic in Malaysia as the country witnessed the surge of sexual related crime and social problem among youths. In relation to this, youths’ knowledge and attitude are the important factor that contribute to this delinquent behaviour and must be addressed as it will shape the youths in the future. The paper discussed the correlation between knowledge and attitude concerning youths in obtaining information on sexual related materials. The research primarily focuses on youths in Malaysia which made up 40% of Malaysia population. The study is significant as it provides a thorough picture how knowledge and attitude influence youths communicate the sexual health topic which is deemed as taboo in Malaysia. The study involved 853 respondents from various demographic group in Malaysia and self-administered questionnaires were distributed and analysed using SPSS to address the research objectives. The result indicated there are significant relationships between knowledge and attitude among youths toward sexual health communication practice. Results showed that 55.1 percent of the studied factors contributed to sexual health communication model among Malaysian youths. Moreover, knowledge and attitude are very critical for the youths to have a better comprehension on sexual health communication. This further testified that Malaysia government and various stakeholders need to acknowledge the importance of sexual health communication and how knowledge and attitude shape positive youth’s development which ultimately contribute to nation building.